(untitled) (Journal of Environmental Science and Natural Resources, 2013)
A study was conducted to evaluate the level of water pollution and its influence on the chemical properties of river water of Dhaka metropolitan city. The water samples were collected from forty five locations of Dhaka metropolitan city during February to March, 2008. Analysis of the major chemical contaminations of river water samples containing Cu, Zn, Mn, As, Pb and Cd was conducted at the Central Laboratory of Bangladesh Agricultural University, Mymensingh. The heavy metal concentrations of river water were recorded as in case of Cu = 0.006 ppm, in case of Zn = 0.021 ppm, in case of Mn = 0.075 ppm, in case of As = 0.003 ppb, in case of Pb = 0.002 ppm and in case of Cd = 0.012 ppm, respectively. The pH of river ranged from 6.28 to 7.61. The EC values were 17.61 to 34.61 ?Scm-1, revealed that all the water samples were low salinity and also excellent for irrigation. According to drinking water (Potable water) and public water standard, Mn and Cd toxicity were detected in river water. For aquaculture standard Mn and Cd were found at harmful level for all living organism. Some water were found unsuitable due to higher concentration of Mn over the recommended limit but other ions like Zn, As, and Pb were within the ’safe limit’. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14842 J. Environ. Sci. & Natural Resources, 5(2): 349-353 2012